Automatic Muscle Segmentation for the Diagnosis of Peripheral Artery Disease Using Multispectral Optoacoustic Tomography - Schillinger, Moritz; Schlereth, Maja; Boraud, Gaspard; Zahnd, Guillaume; Dehner, Christoph; Li, Yi; Kempf, Julius; Caranovic, Milenko; Haney, Briain; Rother, Ulrich; Breininger, Katharina (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
Multispectral optoacoustic tomography (MSOT) is a medical imaging modality capable of visualizing chromophore concentrations, such as oxygenated (HbO2) and deoxygenated hemoglobin (Hb), making it particularly useful for diagnosing blood-perfusion-related diseases like peripheral artery disease (PAD). Previous MSOT-based diagnostic studies involved experts manually selecting a region of interest (ROI) with a predefined shape in the target muscle to analyze blood oxygenation. This study aims to automate this process using a deep-learning-based approach. We present a pipeline that uses co-registered ultrasound images to automatically place an ROI necessary for PAD diagnosis in the MSOT image by training a deep-learning-based segmentation model to locate the target muscle. The resulting segmentation mask is overlaid onto the corresponding optoacoustic image to extract mean HbO2 and Hb intensities within the ROIs. We evaluated our pipeline on two separate PAD-related MSOT-datasets. When comparing blood oxygenation in the automatically generated ROIs on the MSOT images to identify PAD patients, we achieved areas under the ROC curve (AUCs) of 0.87 (vs. 0.85 for manually drawn ROIs) and 0.76 (vs. 0.77 for manually drawn ROIs) on the respective datasets. Our results indicate that optoacoustic ROI placement using deep-learning-based ultrasound segmentation is feasible and performs comparably to manually drawn ROIs by clinical experts. This approach could reduce the annotation effort in future MSOT studies and provide an ROI with greater physiological relevance compared to the arbitrary shapes used in related MSOT research. Future work could extend this approach to other body sites and diseases.
CRIS-Team Scopus Importer:2025-05-16

Detection of wound healing disorders after major amputations by measurements of the microcirculation: A prospective single-center study - Zetzmann, Katharina; Papatheodorou, Nikolaos; Rühl, Eva; Yagshyyev, Shatlyk; Haney, Briain; Moosmann, Oxana; Li, Yi; Meyer, Alexander; Knieling, Ferdinand; Behrendt, Christian Alexander; Lang, Werner; Rother, Ulrich (SAGE Open Medicine, 2024)
Introduction: Although major amputations can often be avoided due to evolving methods of endovascular and surgical revascularizations techniques, in patients with chronic limb-threatening ischemia, it is still necessary in some cases. Aim of this study was the detection of wound healing disorders through intraoperative microcirculation measurements in major limb amputations. Materials and methods: In this single-center clinical study, patients with an indication for major amputation were enrolled prospectively. Cause of amputation, patients’ comorbidities including cardiovascular risk profile were assessed. Macrocirculation, as well as microcirculation were assessed. Microcirculation measurements were performed by fluorescence angiography with the administration of indocyanine green. A preoperative measurement was obtained at the amputation level, followed by three additional measurements of the amputation stump postoperatively. Wound healing was monitored and correlated with the microcirculatory findings, based on the perfusion parameters ingress and ingress rate, calculated in the indocyanine green fluorescence video sequences of the amputation stumps. Results: Forty-five patients were enrolled, including 19 (42%) below-the-knee amputations and 26 (58%) above-the-knee amputations. When considering the need for revision, a change in the microperfusion parameters was observed postoperatively. The mean value for ingress was significantly lower directly postoperatively in stumps requiring revisions (5 ± 0 A.U. versus 40.5 ± 42.5 A.U., p < 0.001). The mean value of ingress rate behaved similarly (0.15 ± 0.07 A.U./s versus 2.8 ± 5.0 A.U./s, p = 0.005). The evaluation of indocyanine green measurements when wound healing disorders occurred also showed nonsignificant differences in the mean values. Conclusion: Fluorescence angiography after major lower limb amputations appears to be an option of depicting microperfusion. Especially, the early postoperative detection of reduced perfusion can indicate a subsequent need for revision. Therefore, this method could possibly serve as a tool for intraoperative quality control after major limb amputation.
CRIS-Team Scopus Importer:2024-08-02
Keywords: fluorescence angiography; indocyanine green; Major limb amputation; microperfusion; wound healing

Independent Factors Influencing Changes in Baroreceptor Sensitivity after Carotid Endarterectomy - Yagshyyev, Shatlyk; Haney, Briain; Li, Yi; Papatheodorou, Nikolaos; Zetzmann, Katharina; Meyer, Alexander; Meyer, Sebastian; Lang, Werner; Rother, Ulrich (Annals of Vascular Surgery, 2024)
Background: Carotid endarterectomy (CEA) is a well-established standard therapy for patients with symptomatic or asymptomatic high-grade carotid stenosis. The aim of carotid endarterectomy is to decrease the risk of stroke and avoid relevant functional loss. However, carotid endarterectomy is known to be associated with hemodynamic dysregulation. In this study we compared eversion CEA (E-CEA) and conventional CEA (C-CEA) regarding postoperative blood pressure values as well as preoperative and postoperative baroreceptor sensitivity in the first 7 days after surgery. The aim was to find possible factors influencing changes in baroreceptor sensitivity. Methods: Patients (111 patients were enrolled, of which 50 patients received C-CEA and 61 patients E-CEA) were prospectively enrolled in this study. For the measurement of baroreceptor sensitivity, a noninvasive Finometer measuring device from Finapres Medical System B.V. (Amsterdam, The Netherlands) was used. Measurements were performed 1 day before surgery (PRE), directly after surgery (F1), on day 1 (F2), day 2 (F3), and on day 7 (F4) postoperatively. Results: Postoperative blood pressure values were significantly higher in the E-CEA group on the day of surgery (F1) (P < 0.001) and on day 1 (F2) (P < 0.001). From day 2 (F3, F4) postoperatively, no significant difference was found between the 2 groups. The invasive blood pressure measurement in the postoperative recovery room showed significantly higher systolic blood pressure values in the E-CEA group (P = 0.001). The need of acute antihypertensive therapy was significantly higher in the recovery room in the E-CEA group (P = 0.020). With regard to changes in baroreceptor sensitivity, significantly lower baroreceptor sensitivity (BRS) values were recorded in the E-CEA group at 1 day (F2) postoperatively (P = 0.005). The regression analysis showed that the applied surgical technique and the patient's age were significant factors influencing changes in baroreceptor sensitivity. Conclusions: In this study we could confirm higher blood pressure levels after E-CEA in the first 2 days after surgery. Additionally, we identified 22 factors possibly influencing baroreceptor sensitivity: surgical technique and age. Based on the data obtained in this study, hemodynamic dysregulation after CEA (E-CEA, C-CEA) is temporary and short-term. Already after the second postoperative day, there was no significant difference between the E-CEA and E-CEA groups, this effect remained stable after 7 days.
CRIS-Team Scopus Importer:2024-08-09

Long-Term Experience of Arterio-Venous Fistula Surgery in Children on Hemodialysis - Almási-Sperling, Veronika; Gall, Christine; Haney, Briain; Latzel, Nina; Knieling, Ferdinand; Hilger, Alina; Regensburger, Adrian; Meyer, Alexander; Lang, Werner; Rother, Ulrich (Journal of Clinical Medicine, 2024)
Background: Arterio-venous fistulas (AVF) are used as first-line access for hemodialysis (HD) in the pediatric population. The aim of this investigation was to describe a single-center experience in the creation of AVF, together with its patency in children. Methods: This single-center retrospective study included all patients aged ≤18 years with AVFs created between 1993 and 2023. The collected data included patients’ demographics, hemodialysis history, intraoperative data, and required reinterventions in order to determine the impact of these variables on primary, primary-assisted, and secondary patency. Results: Fifty-seven patients were analyzed with a median age of 15 years (range, 7–18 years). Fifty-four forearm and four upper arm fistulas were performed. The median follow-up was 6.9 years (range, 0–23 years). The primary failure rate was 10.5%. The primary patency rate was 67.6%, 53.6%, 51.4%, and 38.1% after 1, 3, 5, and 10 years; primary-assisted patency was 72.9%, 62.8%, 60.6%, and 41.5%; and secondary patency was 87.3%, 81.3%, 76.8%, and 66.6% after 1, 3, 5, and 10 years in the studied population. Conclusions: AVFs showed an acceptable rate of primary failure and excellent long-term patency. In this context, AVFs are an appropriate option for HD access, especially in pediatric patients.
CRIS-Team Scopus Importer:2024-07-12
Keywords: arterio-venous fistula; children; long term; primary patency; secondary patency

Teachability of multispectral optoacoustic tomography - Li, Yi; Gröhl, Janek; Haney, Briain; Caranovic, Milenko; Lorenz-Meyer, Eva; Papatheodorou, Nikolaos; Kempf, Julius; Regensburger, Adrian; Nedoschill, Emmanuel; Bühler, Adrian; Siebenlist, Gregor; Lang, Werner; et al. (Journal of Biophotonics, 2024)
To date, the appropriate training required for the reproducible operation of multispectral optoacoustic tomography (MSOT) is poorly discussed. Therefore, the aim of this study was to assess the teachability of MSOT imaging. Five operators (two experienced and three inexperienced) performed repositioning imaging experiments. The inexperienced received the following introductions: personal supervision, video meeting, or printed introduction. The task was to image the exact same position on the calf muscle for seven times on five volunteers in two rounds of investigations. In the first session, operators used ultrasound guidance during measurements while using only photoacoustic data in the second session. The performance comparison was carried out with full-reference image quality measures to quantitatively assess the difference between repeated scans. The study demonstrates that given a personal supervision and hybrid ultrasound real-time imaging in MSOT measurements, inexperienced operators are able to achieve the same level as experienced operators in terms of repositioning accuracy.
CRIS-Team Scopus Importer:2024-05-17
Keywords: MSOT; multispectral optoacoustic imaging; teachability; ultrasound